A comprehensive analysis of constitutive naturally processed and presented HLA‐C*04:01 (Cw4) – specific peptides. Issue 3 (7th January 2014) - Schittenhelm, R. B.; Dudek, N. L.; Croft, N. P.; Ramarathinam, S. H.; Purcell, A. W.
Abstract The human B lymphoblastoid cell line C1R is widely regarded as human leukocyte antigen‐A (HLA‐A)/HLA‐B negative and is therefore frequently exploited as a recipient cell line to study HLA class I functions. However, the normal levels of HLA‐C*04:01 often hamper the investigation of introduced HLA class I allomorphs, which is particularly evident in sensitive applications such as mass spectrometry. Here we describe the comprehensive analysis of endogenous HLA‐C*04:01 ligands expressed on the surface of C1R cells to (i) define a large sequence dataset of HLA‐C*04:01 ligands, to (ii) refine the HLA‐C*04:01 peptide‐binding motif and (iii) to provide a resource that allows discrimination between peptides bound to introduced HLA class I subtypes and to the endogenous HLA‐C*04:01 molecules.